Digital Community of Children’s self-injuries in TikTok: Quantitative and qualitative methodological approach - Martín Muñoz, Diego; Atauri Mezquida, David (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Non-Suicidal Self-Injury is a growing phenomenon in social networks, affecting an average of 30% of young people in Spain. Therefore, we present a methodology applied for the identification and analysis of the content created by young people in TikTok. On the one hand, through a quantitative study, an API is used to collect and classify multimedia content through hashtags. On the other hand, a qualitative analysis that elaborates a systemic study of them. Thus, the objective is to identify the contents on TikTok related to Non-Suicidal Self-Injury and to understand their codes.